Motivación y productividad en los trabajadores de la Caja Piura Iquitos 2024 - Irarica Huaymacari, Junior (2025)
The study aimed to determine the relationship between motivation and productivity among workers at Caja Piura, Iquitos, 2024. A quantitative approach was used with a descriptive, non-experimental, and correlational design, observing the variables without manipulation to analyze their relationship. The reliability measurement of the variables through the Cronbach's Alpha coefficient showed values of 0.881 for motivation and 0.874 for productivity, indicating high internal consistency in the scales used. The Spearman correlation analysis (Rho = 0.975**) revealed a very strong positive relationship between motivation and productivity, with a bilateral significance level of 0.000, confirming the proposed hypothesis. These findings emphasize that motivation, both intrinsic and extrinsic, is a key factor in job performance, demonstrating that its improvement directly impacts productivity. Among the study's novel aspects, the detailed analysis of intrinsic and extrinsic motivation dimensions stands out, highlighting their significant influence on work performance. It is concluded that implementing organizational strategies that promote personal development, internal recognition, and external incentives can optimize work performance in the financial sector. This study provides a solid foundation for designing human resource policies aimed at enhancing productivity through motivation, offering relevant practical and theoretical implications for similar organizations.